Survival Strategies of Traditional Retailers during the COVID-19 Pandemic: Some Insights from a Developing Country - Sopha, Bertha Maya; Arvianto, Ary; Tjahjono, Benny (2022)
Purpose: The paper aims to report the impact of the COVID-19 pandemic and investigate survival strategies during the pandemic of traditional retailers. Design/methodology/approach: Exploratory methodology consisting of the literature review and an empirical study was conducted. The theoretical framework of resilience strategy was built to provide a guideline for the empirical study. The empirical study involves a longitudinal study with 30 traditional retailers located in Yogyakarta, Indonesia. The empirical data was collected using semi-structured interviews in mid-2019 and mid-2020, corresponding to the condition before and during the pandemic. Secondary data sources were also examined to refine the empirical evidence. Findings: The findings confirm that the pandemic has created disruptions in supply and demand, subsequently affecting operations. 90 of the traditional retailers experienced demand reduction, which varied among the retailers (M = 47, SD = 25), and 10 of the traditional retailers have not received any profit. The majority of the traditional retailer adopted reactive rather than proactive strategies. To cope with the pandemic, the traditional retailers have focused on efficient strategies and implemented exploitation-oriented strategies combined with exploration-oriented strategies. Trust and social capital were also discovered to explain the reasons behind the resiliency and sustainability of the traditional retailers. Research limitations/implications: Due to the preliminary and explorative nature of the present study, the generality of the findings may therefore be limited. Future research focusing on quantitative analysis using a large sample helps to achieve the generality of the findings. Practical implications: Because the strategies implemented in large enterprises (LEs) usually do not fit in micro-, small-, and medium enterprises (MSMEs), exploring strategies that are consistent with the characteristics of MSMEs and leverage their potentials is necessary. Building ambidextrous retailers through leveraging social capital/network and informal forum, exploiting affordable technology (e.g., social media, marketplace), and honing innovativeness is a way to survive in a dynamic environment. Social implications: Because the traditional retailers have contributed to economic development and social function, the government should empower them to leverage their capabilities through training and strengthen their business ecosystem through collective actions. Originality/value: The study contributes to the resilience body of knowledge concerning the strategies implemented by the traditional retailers during a long and unpredictable disruption in a developing country setting, which is scarce in the literature. © 2022, OmniaScience. All rights reserved.